2021
DOI: 10.1038/s41598-021-91959-w
|View full text |Cite
|
Sign up to set email alerts
|

Short term fluctuating temperature alleviates Daphnia stoichiometric constraints

Abstract: In this study, we analysed how short term temperature fluctuation interacts with nutrient limitation in the vertical migrating Daphnia commutata. We hypothesize that short term (daily) temperature fluctuation will alleviate nutrient limitation. We carried out experiments analysing growth rates, phosphorus and RNA content of D. commutate grown under four different temperature regimes and two P-limited conditions. Our experiments showed that individuals grown under fluctuating temperature grew more than at the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…We observed that body C:P stoichiometry changes significantly with temperature, as indicated in previous work (Balseiro et al, 2021;Kendrick & Benstead, 2013;Woods et al, 2003) but in contrast to Ruiz et al (2020). Body C:P had a nonlinear U-shaped thermal response, with a minimum C:P located at the MaxTER C:P temperature.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We observed that body C:P stoichiometry changes significantly with temperature, as indicated in previous work (Balseiro et al, 2021;Kendrick & Benstead, 2013;Woods et al, 2003) but in contrast to Ruiz et al (2020). Body C:P had a nonlinear U-shaped thermal response, with a minimum C:P located at the MaxTER C:P temperature.…”
Section: Discussionsupporting
confidence: 59%
“…Growth rate increases with increasing temperature and is in part responsible for the increase in ingestion, due to the extra demands for substrates (Hayes et al, 2015). Body C:P is expected to increase with temperature (Balseiro et al, 2021;Woods et al, 2003), while for GGEs decreasing, increasing and constant thermal responses were reported (Doi et al, 2010;Hagerty et al, 2014;Smith et al, 2021;Ye et al, 2019;Zheng et al, 2019). Based on these hypothesised mechanisms, we predict that ectotherm nutrient requirements change with temperature in a nonlinear fashion, as a response to nonlinear thermal reaction norms of metabolism and growth.…”
Section: Introductionmentioning
confidence: 87%